A legal analysis of cases prosecuted by the pharmacy enforcement division in Kuala Lumpur and Selangor for the years 2006-2007 / Zaidi Ahmad, Mohd Azaruddin Azis and Kamaruzzaman Othman - Ahmad, Zaidi; Azis, Mohd Azaruddin; Othman, Kamaruzzaman (Faculty of Law, 2008)
This study is a legal analysis of cases prosecuted by the Pharmacy Enforcement Division in Kuala Lumpur and Selangor for the years 2006 and 2007. The objectives of the study are to identify the pattern of cases prosecuted by the Pharmacy Enforcement Division and to determine legal issues and problems transpired in those cases. This study obtained the prosecution data from the PED headquarters in Petaling Jaya, Kuala Lumpur and Selangor. The data were then analysed to determine a pattern. Once the pattern was identified, the questions for the interviews were developed. Then interviews were conducted in order to identify the legal issues and problems that had transpired in those cases. The interviewees consisted of three senior officers from PED who conducted the prosecution, a Deputy Public Prosecutor who gave the sanction to prosecute and two Magistrates who normally presided on the PED' cases. There are four patterns identified: most prosecution cases are SODA cases, most prosecution cases ended with PG, most Psychotropic cases claim trial and most sentence passed is low. The legal issues identified are an inadequate sentence provided by certain acts and an inadequate sentence passed by the court. In additional, the problems identified are the officers do not give any submission and lack of training and exposure. Finally, this study recommends that the officer conducting the prosecution should give a submission for a heavier sentence, an amendment to the penalty section of the acts which provide a low sentence, and emphasis on training for the PED officers not just on the prosecution but also on the enforcement of law as a whole.